Sosiologi Pendidikan: Analisis Konflik Pembangunan Pagar Laut Tangerang Selatan - Amaliyah, Amaliyah (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The construction of the sea fence in South Tangerang has become a national issue, with the 30.16 km fence lacking clear accountability. This phenomenon is also observed in other regions, such as Kamal Muara in North Jakarta, Batam, Sidoarjo, Surabaya, and Bekasi. The sea fence case has the potential to erode public trust in the government's ability to enforce law and deliver justice. This research aims to identify the conflicts between the community and the government in the construction of the sea fence in South Tangerang and to explore effective strategies for managing these conflicts. The study employs a qualitative library research method, which involves reviewing and analyzing existing literature, documents, reports, and other secondary sources relevant to the case. By synthesizing various viewpoints and theoretical frameworks, the research uncovers the internal and external factors, as well as political influences, that contribute to the conflict. The findings suggest that the conflict arises from a combination of communication barriers, lack of public participation, and an imbalance of power between the government and the local community. The study identifies strategies for managing the conflict, including improving communication and public participation in the development process, and ensuring that both governmental and public interests are balanced through principles of justice, transparency, flexibility, and inclusiveness. Additionally, the research proposes solutions to address the sea fence issue, focusing on legal aspects, transparency in information dissemination, and the recommendation for continuous social education and collaboration among academics, government, NGOs, businesses, and the public.